Interferentzia, hiztun garbien galera eta mintzaldaketa: Hiriart-Urrutiren garaiko zenbait korrelato - Zalbide, Mikel (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2009)
Language contact often results in three different types of outcome: a jump from language maintenance to language shift in the use of the languages at work, an increase in the numbers of bilinguals with varying language dominance configurations in the speech communities involved (in one of them, at least) and an intensification of interference and similar novelties with regard to the internal composition of the language. The journalist Hiriart-Urruti (1859-1915) was fairly familiar with instances of those three planes. His society was moving rapidly from the spread of French to language shift towards it: he attempted to reflect that on a number of occasions. When he did so, he often strove to give a structured presentation of events as they unfolded, without much technical terminology. To that effect he used specific outlooks and drew specific consequences. In addition, he occasionally believed he could detect the underlying logic of events. This article seeks to inform about those outlooks, main consequences and underlying logical concatenations.